Pattern reconfigurable antenna for radar applications - Razak, Arrauzah (2015)
Reconfigurable antennas change polarization, operating frequency, or far-field pattern in order to cope with the changing of system parameters. Based on pattern reconfigurability, the frequency band remains unchanged while the radiation pattern changes based on system requirements. Using fixed or omnidirectional antenna is wasting the usage power. For fully utilize the power, pattern reconfigurable is proposed. The objective of this project is to design pattern reconfigurable antenna by means of switches. The antenna used in this project is a Vivaldi antenna with operating frequency at 2.4 GHz. The computer simulation package CST Microwave Studio 2014 software is used for the antenna structure design and simulation. The prototype is fabricated on a FR4 substrate. From the simulation and fabricated antenna, the beam peak direction of the patterns can be reconfigured to the right and left side by activating or deactivating the switches